Closeness and Conflict With the Deceased: Exploring the Factor Structure of the Quality of Relationships Inventory in a Bereaved Student Sample. (September 2019) - Bottomley, Jamison S.; Smigelsky, Melissa A.; Floyd, Randy G.; Neimeyer, Robert A.
With mounting empirical evidence that interpersonal closeness and conflict with the deceased prior to death are significant predictors of grief reactions following loss, accurate empirical examination of these two constructs is of high importance. Despite the utility of the Quality of Relationships Inventory (QRI) in numerous domains of research, the original instrument was not constructed with a predeath, mourner–decedent relationship in mind. Therefore, this study clarified the factor structure of a modified QRI focusing on major dimensions of the predeath relationship with the deceased—dynamics that could have strong implications for the survivor's bereavement trajectory. An exploratory factor analysis of 386 bereaved adults revealed two salient factors, deemed closeness and conflict. These results suggest that the modified bereavement version of the QRI, designated the Quality of Relationships Inventory–Bereavement version, is well positioned to advance research in thanatology, with possible limitations noted in the range of relationships to which it is applicable.